2009
DOI: 10.21273/jashs.134.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Breeding on the Genetic Diversity of Cultivated Strawberry as Revealed by Expressed Sequence Tag-derived Simple Sequence Repeat Markers

Abstract: Unlike other important crops analyzed so far for genetic diversity and population structure, the brief history and particularities of the genetics of the cultivated strawberry (Fragaria ×ananassa Duchesne) have limited its genetic characterization. The genomic composition and the pattern of inheritance have not been fully elucidated, although a number of studies have suggested a highly diploidized genome. In this study, the similarity relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 45 publications
5
21
1
Order By: Relevance
“…The value of heterozygosity is in fact the percentage of polymorphic SNPs; thus, it is not surprising that the value is somewhat lower than that found with 24 SSR markers in garden roses (Vukosavljev et al, 2013). Unlike many other cultivated plant species (Kilian et al, 2007; Gil-Ariza et al, 2009; Wang et al, 2010; Gross et al, 2014), we did not see a reduction over time when we considered the year of release of the variety. This may corroborate observations on the sensitivity of rose for inbreeding depression, which makes selfing unsuitable as a breeding strategy (Pipino et al, 2011).…”
Section: Discussioncontrasting
confidence: 68%
“…The value of heterozygosity is in fact the percentage of polymorphic SNPs; thus, it is not surprising that the value is somewhat lower than that found with 24 SSR markers in garden roses (Vukosavljev et al, 2013). Unlike many other cultivated plant species (Kilian et al, 2007; Gil-Ariza et al, 2009; Wang et al, 2010; Gross et al, 2014), we did not see a reduction over time when we considered the year of release of the variety. This may corroborate observations on the sensitivity of rose for inbreeding depression, which makes selfing unsuitable as a breeding strategy (Pipino et al, 2011).…”
Section: Discussioncontrasting
confidence: 68%
“…As an example, pedigrees of 134 North American cultivars were traced and shown to originate from only 17 cytoplasmic sources [25]. Despite introgressions of wild strawberry germplasm increased initial diversity of the cultivated strawberry, loss of diversity was observed in modern strawberry cultivars [26,27]. However, our results showed that advanced lines can display large variability from high to low level of resistance (Table 5).…”
Section: Discussionmentioning
confidence: 77%
“…Since cultivated strawberry breeding began in the 1800s using a small number of lines (Darrow, 1966), the diversity of F. ×ananassa has been increased and its genome reshaped by repeated interspecific hybridization with phylogenetically diverse F. chiloensis and F. virginiana accessions (Darrow, 1966;Gil-Ariza et al, 2009;Hardigan et al, 2018;Liston et al, 2014;Hancock, 1999;Bringhurst and Voth, 1984;Hancock et al, 2002;. Introgression of beneficial alleles from these species also results in the accumulation of unfavorable alleles in cultivated strawberry.…”
Section: Discussionmentioning
confidence: 99%